COVID-19 safety recommendations for the reopening of the Dr. Joaquim Grava Corinthians training facility - Ramos e Côrte, A. C.; Grava de Sousa, J. P.; Grava de Sousa, I.; Muarrek Garcia, R.; Stancati, J. (Revista Brasileira de Medicina do Esporte, 2020)
Since December 2019, the world has been fighting the SARS-CoV2 virus (severe acute respiratory syndrome coronavirus 2). Little is known about vaccines and forms of treatment at this point. However, the importance of preventing transmission is very clear, and one of the main measures is social isolation. Major sports tournaments, including soccer championships, have been suspended or cancelled due to COVID-19, on the grounds of our understanding of the importance of social isolation. Accordingly, large clubs have handed over their stadiums for the construction of field hospitals, and have encouraged health care by providing guidance on hygiene and social distancing. The involvement of soccer in the prevention of this pandemic is due to the fact that its managers understand the importance of this sport in the process, and its influence on fans and players. Over the years, soccer has incorporated scientific and technological knowledge into the game, which has frequently served as a role model for other types of sport and for the population. Therefore, in these extreme times of the COVID-19 pandemic, there is no reason to believe it would be any different, and standpoints taken by soccer teams serve as an example and reiterate their role in the educational commitment to society and respect for government authorities. As a result, a protocol was drawn up for the resumption of training, in which all recommendations to be followed by players, managers/backroom staff and employees are in accordance with official health agencies of the national and international government. In other words, the resumption of training is subject to the authorization of government authorities.